A Comparative Study on the Distributions of Incoherent and Coherent Plasmaspheric Hiss. Issue 7 (5th April 2021) - He, Zhaoguo; Yu, Jiang; Li, Kun; Liu, Nigang; Chen, Zewen; Cui, Jun
Abstract: We perform a comparative study on the distributions of incoherent and coherent plasmaspheric hiss, based on the Van Allen Probe data. The statistics show that incoherent hiss (∼10–20 pT) is widely distributed in dayside plasmasphere, with peak frequencies below 500 Hz; intense coherent hiss (amplitudes up to 80 pT) occurs in outer plasmasphere of L > 4 ( L denotes the L‐shell.), whose frequency increases with ambient magnetic field significantly. The Poynting flux analysis indicates that incoherent hiss generally propagates omni‐directionally inside the plasmasphere, with features of external sources; the coherent hiss propagates away from the equatorial region in outer plasmasphere and has a reversed direction in inner plasmasphere, indicating two different wave sources by local generation and ducted lightning generated whistler, respectively. This comparative study helps us to better understand the origination of plasmaspheric hiss. Plain Language Summary: Coherence level is an important parameter to identify the sources of plasmapheric hiss. Plasmaspheric hiss has long been regarded as an incoherent emission excited from external sources. Recent studies suggested that coherent hiss generated locally could be common phenomena in the plasmasphere. Therefore, plasmaspheric hiss in different coherence levels should present different distribution features. Here, we perform a comparative study on the distributions of incoherent and coherent plasmaspheric hiss, based on the Van Allen Probe data. The results show that the incoherent hiss is distributed in a wide range inside the plasmasphere with peak frequencies below 500 Hz, and the intense coherent hiss prefers to occur in outer plasmasphere with frequencies increasing as ambient magnetic fields. Based on the wave normal angle and Poynting flux analysis, the incoherent hiss may be originated from outside of plasmasphere due to the omni‐directional propagation properties. The coherent hiss propagates away from the equatorial region in outer plasmasphere and has a reversed direction in inner plasmasphere, indicating two different wave sources by local generation and ducted lightning generated whistler, respectively. This comparative study helps us to distinguish the distributions of plasmaspheric hiss with different coherence levels and provides us a new insight into their origination. Key Points: A comparative study on the distributions of incoherent and coherent plasmaspheric hiss is presented for the first time Incoherent hiss occurs in a wide range of dayside plasmasphere, propagating in both directions along with the magnetic field Intense coherent hiss is more likely to occur in outer plasmasphere of L > 4, propagating away from a local source of the equatorial region